2002
DOI: 10.1097/00004694-200205000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Various techniques for improving the success of needle placement in hip arthrography have been described. The authors describe a simple consistent sign that occurs in both subluxated and dislocated hips and is present only when the needle is correctly placed within the hip joint. This, in conjunction with other techniques, has improved their quality of hip arthrography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Yun et al 11 reported the suction-bubble technique, in which the movement of air bubbles can be visualized in the attached tubing. Straw et al 12 reported a method based on adduction signs. According to their method, saline is injected into the hip with the patient in the frog-leg position: if the needle is correctly placed, then, when the joint is distended, the knee will rise (adduct) from the operating table.…”
Section: Discussionmentioning
confidence: 99%
“…Yun et al 11 reported the suction-bubble technique, in which the movement of air bubbles can be visualized in the attached tubing. Straw et al 12 reported a method based on adduction signs. According to their method, saline is injected into the hip with the patient in the frog-leg position: if the needle is correctly placed, then, when the joint is distended, the knee will rise (adduct) from the operating table.…”
Section: Discussionmentioning
confidence: 99%